Translation of German Relative Clauses in The Fairy Tale Die Bremer Stadtmusikanten by Students of the German Department, Faculty of Letters, Malang State University - Rosyidah, Rosyidah; Shafira Adhiningsih Bhakti Pertiwi (Nexus Publishing NXP, 2024)
Relativsatz or German relative clause is a special subordinate clause because of its structure, which often makes it difficult for students to understand, use and translate. The aim of this study is to describe the translation of Relativsätze or Relativpronomen in the fairy tale Die Bremer Stadtmusikanten by German Department students at the Faculty of Letters of Malang State University. The descriptive qualitative method was used. The data are Relativsätze and their translation in the data sources, the source text and the target text. The data were collected using documentation techniques and analysed interactively using Miles and Huberman's method. The results show that there are 9 Relativsätze with 5 Relativpronomen in the fairy tale, namely welcher, der, die, wo and was. In general, the relative clauses were translated by changing them to Kalimat Relatif (Indonesian relative clauses) with different Pronomina Relatif (Indonesian relative pronouns) and to non relative clauses.